Evaluating Veterans' Preferences for Renal Denervation for Treatment of Difficult‐to‐Control Hypertension: A Single‐Center Survey Study - Benjamin L. Magod; Peter A. Glynn; Wesley J. Manz; Pal V. Shah; Mladen I. Vidovich (Health Science Reports)
ABSTRACT Background and Aims Catheter‐based renal denervation (RDN) is a safe and effective alternative treatment for hypertension. However, data on patient preferences are limited. This study sought to delineate preferences for RDN among Veterans with difficult‐to‐control hypertension at an urban VA Medical Center with the goal of optimizing management and referral practices in hypertensive Veterans. Methods Patients on 3+ antihypertensive medications and a measured creatinine < 2.5 mg/dL were identified from the pharmacy database. A total of 100 randomly selected patients were telephoned for the administration of a survey assessing patient preferences for RDN, expectations for RDN, as well as medication adherence using the Medication Adherence Report Scale (MARS‐5). Additional chart review was performed to gather demographic and clinical data of survey respondents. Results A total of 51 Veterans completed the survey. While 29 (56.9%) Veterans indicated a preference against RDN, 22 (43.1%) indicated a preference for this procedure, and 33 (64.7%) expressed that if their blood pressure were uncontrolled, they would prefer RDN over additional medication. A history of congestive heart failure (p = 0.017) and lower MARS‐5 score (p = 0.007) were associated with a preference for RDN. Age, reported medication side effects, and hypertension treatment satisfaction ratings were not associated with preference for or against RDN. Conclusions A considerable portion of Veterans with difficult‐to‐control hypertension at an urban VA Medical Center expressed a preference for RDN if their blood pressure were to be uncontrolled or if recommended by their doctor. These survey results should be considered in shared decision‐making discussions for hypertension management in this population.